ISLAMIC MICROECONOMICS DESIGN: ISLAMIC MICROECONOMICS DESIGN - Yumni Alfiah Rihadatulaisy; Nana Herdiana Abdurrahaman; Eri Novari (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2023)
Islam has regulated all aspects of human life, including in the economic field. Today Islamic Economic thought has experienced rapid development and comprehensive coverage. At this level of development, the material can be obtained to compile the concept of the Islamic economic system, both micro, and macro. The purpose of this journal is to find out the design of Islamic microeconomics. The research method used by researchers in this study is a qualitative approach which is library research. The data collection technique is by conducting a review study on literature with a problem to be solved. Thus, it can be concluded that Islamic economics is likened to a house, building, or building that requires a value, principle, and basic concept in the form of design before the economic system is built. By knowing an Islamic economic design, it is hoped that you can get a complete and comprehensive picture briefly about the Islamic economy which is like a building and consists of a roof, pole, and foundation. There are basic principles in the design of Islamic economics. Some of these principles can generally be divided into three parts, namely: universal values, derivative principles, and morals.